The effect of using learning portal on primary school students in the subject of design and technology - Ali, Azita; Abdul Rashid, Intan Shariena; Ea, Suk Yong (HRPUB, 2019)
Design and Technology (DST) were introduced at the Primary School as more emphasis is being placed on technical and vocational skills nowadays. However, the use of conventional teaching methods and the lack of teaching aids have triggered students’ low achievement in the DST subject. This study was conducted to identify the effect of using DST learning portal on students’ achievement compared with using conventional teaching method. A DST learning portal was developed and used as an independent variable in this study. A total of 32 year 4 students from a Primary School were selected as respondents by purposive sampling method. This study is quasi-experimental research which uses pre and post-test as an instrument to identify the achievement of students before and after using different learning methods in the DST subject. In addition, questionnaire and observation checklist were used to collect students' perceptions about the usability of DST learning portal. The data were analysed descriptively by using quantitative approach. The results of the independent t-test showed that there was no significant difference in pre-test achievement between treatment group (M = 23.8, SD = 12.6) and control group (M = 25.0, SD = 14.1); t (30) = 0.64, p = 0.79, while Mann Whitney U test results showed that the post-test achievement of treatment group was higher than the control group after using DST learning portal (U = 7.500, p = .000). The level of usability of the learning portal was very high according to the score obtained from the questionnaire (88.15%) and the checklist (84%). These findings show that the DST learning portal has a very high level of usability and the use of portal can significantly improve students’ achievement in DST subject.